Antioxidant activity, total phenolic and flavonoid content of several indigenous species of ferns in East Kalimantan, Indonesia - HENNY NURHASNAWATI; REKSI SUNDU; SAPRI SAPRI; RISA SUPRININGRUM; HARLINDA KUSPRADINI; ENOS TANGKE ARUNG (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Nurhasnawati H, Sundu R, Sapri, Supriningrum R, Kuspradini H, Arung ET. 2019. Antioxidant activity, total phenolic and flavonoid content of several indigenous species of ferns in East Kalimantan, Indonesia. Biodiversitas 20: 576-580. This study aimed to determine the total phenolic and flavonoids content and antioxidant activity of ethanol extract of several indigenous species of ferns in East Kalimantan. Total phenolic content was determined by Folin-Ciocalteau method and flavonoid content was measured by colorimetric method. Antioxidant activity was evaluated by DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The result of photochemical screening indicated that the leaves of Plagiogyria pycnophylla, Plagiogyria glauca, and Stenochlaena palustris contained alkaloid, flavonoid, tannin, saponin, and steroid while Acrostichum aureum contained flavonoid, tannin, saponin and steroid. The result showed extract Acrostichum aureum had the highest total phenolic content (366.4573 ± 2.2117 mg GAE.g-1), flavonoid content (228.6087 ± 2.2548 mg QE.g-1), and very strong antioxidant activity with IC50 value 29.5303 ppm. There is positive correlation between total phenolic content, flavonoid with antioxidant activity.